High-resolution MEMS inclinometer based on pull-in voltage - Alves, Filipe Manuel Serra (2015)
High-resolution pull-in-based microelectromechanical system (MEMS) inclinometers are presented in this paper. Pull-in is characterized by the sudden loss of stability in electrostatically actuated parallel-plate structures, and since pull-in voltage is stable and easy to measure, it enables an effective transduction mechanism that does not require complex and stable capacitive readout electronics. The MEMS devices used to test the novel architecture have differential actuation electrodes resulting in two pull-in voltages that change differentially with applied acceleration. Dedicated MEMS microstructures with extra proof mass show high sensitivity; 269 mV/degrees with a nonlinearity <0.5% FS (Full Scale of +/-23 degrees). The measured noise is limited by the actuation mechanism, setting the sensor's resolution at 75 mu degrees; high above state-of-the-art MEMS devices.